Analysis Of Donor Satisfaction Toward The Services Of An Infaq Management Institution Using Importance Performance Analysis And Customer Satisfaction Index Methods - Ali Hamdan; Saifuddin; Jaenudin, M (ICO EDUSHA, 2025)
This paper aims to analyze donor satisfaction with the services of an Infaq Management Institution using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. In this study, a survey of 100 donors was conducted to collect data regarding their expectations and experiences with the provided services. The IPA method was used to identify factors influencing donor satisfaction, while the CSI method was applied to measure the overall level of satisfaction. The analysis results indicate that several service elements need improvement, including transparency in the reporting of infaq fund usage and responsiveness to donor inquiries. The physical evidence dimension was excluded from the analysis because it did not meet the reliability test (Cronbach’s Alpha < 0.6). The validity test results show that all questionnaire items are valid (P-value < 0.05). The CSI score of 70.57% indicates that, in general, donors are satisfied with the services of the Infaq Management Institution (LMI). Based on the IPA analysis, there were no attributes in the main priority quadrant (Quadrant I), but four attributes should be maintained because of their high performance and high importance (Quadrant II), namely the implementation of the 3S principle (Smile, Greet, Serve), transparency in fund management, accuracy of fund allocation, and confidentiality of donor data. On the other hand, six attributes fall into the low-priority quadrant (Quadrant III), indicating potential improvements in reporting and communication aspects. These results provide strategic insights for LMI to maintain its service excellence and enhance areas that are still suboptimal to sustain and increase donor loyalty. This study provides recommendations for infaq management institutions to improve service quality to enhance donor satisfaction. Keywords: Donor Satisfaction, Infaq Management Institution, Importance Performance Analysis, Customer Satisfaction Index.